Diverse morphologies of zinc oxide nanoparticles and their electrocatalytic performance in hydrogen production - Sofianos, Veronica; Lee, Juni; Silvester-Dean, Debbie; Samanta, P.K.; Paskevicius, Mark; English, N.J.; Buckley, Craig (ELSEVIER, 2021)
Hydrogen is considered an attractive alternative to fossil fuels, but only a small amount of it is produced from renewable energy, making it not such a clean energy carrier after all. Producing hydrogen through water electrolysis is promising, but using a cost-effective and high-performing catalyst that has long-term stability is still a challenge. This study exploits, for the first time, the potential of zinc oxide nanoparticles with diverse morphologies as catalysts for the electrocatalytic production of hydrogen from water. The morphology of the nanoparticles (wires, cuboids, spheres) was easily regulated by changing the concentration of sodium hydroxide, used as the shape controlling agent, during the synthesis. The spherical morphology exhibited the highest electrocatalytic activity at the lowest potential voltage. These spherical nanoparticles had the highest number of oxygen vacancies and lowest particle size compared to the other two morphologies, features directly linked to high catalytic activity. However, the nanowires were much more stable with repeated scans. Density-functional theory showed that the presence of oxygen vacancies in all three morphologies led to diminished band gaps, which is of catalytic interest.